BUDAYA TRI HITA KARANA SEBAGAI PEMODERASI PENGARUH PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA LEMBAGA PERKREDITAN DESA DI KOTA DENPASAR - Mulyawan, I Putu Arya; Wirama, Dewa Gede; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study analyses the influence of good corporate governance (GCG) on the performance of Lembaga Perkreditan Desa (LPD) and to test whether Tri Hita Karana (THK) Culture moderate that influence. GCG is measured by questionnaires on five GCG principles, namely transparency, accountability, responsibility, independency, and fairness. THK is measured by questionnaires on three aspects of THK namely parahyangan, pawongan, and palemahan. LPD’s performance is measured by CAMEL scores as reported by LPLPD Kota Denpasar as of December 2016. Data analysis technique used to test the effect of GCG on LPD’s performance is simple linear regression analysis. A moderated regression analysis is used to analyse whether THK moderate the influence of GCG on LPD’s performance. The result of the data analysis shows that GCG has a positive effect on LPD’s performance, and THK strengthens the influence of GCG on LPD’s performance in Denpasar City.